The Viability of Mobile Services (SMS and Cell Broadcast) in Emergency Management Solutions: An Exploratory Study - Al-dalahmeh, Mahmoud; Al-Shamaileh, Ons; Aloudat, Anas; Obeidat, Bader Yousef (International Journal of Interactive Mobile Technologies (iJIM), 2018)
In this paper the path forward in location-based mobile phone warning systems is given against a concise backdrop of their deployment worldwide. Of relevance here is (i) how the systems are implemented using legislation, contractual service level agreement instruments or a hybrid approach, (ii) whether or not governments who deploy these systems will carry the cost of the deployment during an emergency or disaster, and (iii) whether or not carrier participation is mandated. Of particular importance are also the underlying technologies of this kind of emergency systems. To date, the short message service and cell broadcast service have been the main technologies to be utilised by governments in the application of location-based services in modern emergency management solutions. However, these technologies will most certainly be superseded by newer, more powerful capabilities. A comprehensive list of requirements for the future location-based emergency systems is presented also in this paper. In essence, these are recommendations to be adhered to if robust solutions using new technologies are to be deployed in a nation state.